2020
DOI: 10.3390/toxins12030182
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Contamination Concerns of Herbs and Medicinal Plants

Abstract: Plants and medicinal herbs that are available on the market do not always meet quality and safety standards. One particular concern is the risk of contamination with mycotoxins. Aflatoxins and ochratoxin A are the most frequently described mycotoxins in herbal products and have repeatedly been reported to occur at concentrations which exceed regulatory levels set by the European Union (EU). Possible solutions include enforcing existing limits, and for the new materials, establishing tighter limits and mandate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 60 publications
0
28
0
2
Order By: Relevance
“…Nowadays, several studies have reported the presence of mycotoxins in herbal plants and derivative products, considering that this contamination is a global issue, particularly in developing countries [ 5 ]. In fact, previous investigations reported that, under specific conditions, toxigenic fungal species from Aspergillus, Penicillium, Fusarium, and Alternaria genus can generate mycotoxins and contaminate herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, several studies have reported the presence of mycotoxins in herbal plants and derivative products, considering that this contamination is a global issue, particularly in developing countries [ 5 ]. In fact, previous investigations reported that, under specific conditions, toxigenic fungal species from Aspergillus, Penicillium, Fusarium, and Alternaria genus can generate mycotoxins and contaminate herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increased demand for the use of plant extracts and their compounds and this raises concerns about the safety, toxicity and quality of these products. Studies have reported the contamination of plant materials with medicinal properties by mycotoxins ( Ashiq et al., 2014 ; Mulaudzi, 2019 ; Altyn and Twaruzek, 2020 ; Thipe et al., 2020 ). Furthermore, research has shown that many plant extracts used in traditional medicine and as food ingredients are toxic and mutagenic.…”
Section: Mitigation Of Toxigenic Fungi and Mycotoxins Using Botanicalmentioning
confidence: 99%
“…However, overuse of these synthetic substances may have a long influence on environmental pollution and human health issues. The reported liver effects of pesticide and herbicide residues include hepatocellular hypertrophy and cytoplasm degeneration, obstructive cholestasis, decreased acetylcholinesterase activity, and hepatic mitochondrial toxicity [ 114 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ].…”
Section: Nonphyto-hepatotoxins From Hmpsmentioning
confidence: 99%